An occupation-based strategy training approach to managing age-related executive changes: a pilot randomized controlled trial. (February 2014) - Dawson, Deirdre; Richardson, Julie; Troyer, Angie; Binns, Malcolm; Clark, Amanda; Polatajko, Helene; Winocur, Gordon; Hunt, Anne; Bar, Yael
Objective: To determine the feasibility of recruitment and retention of healthy older adults and the effectiveness of an intervention designed to manage age-related executive changes. Design: A pilot randomized controlled trial. Setting: Research centre and participants' homes. Participants: Nineteen healthy, community dwelling older adults with complaints of cognitive difficulties and everyday problems, but no evidence of mild cognitive impairment, dementia or depression on objective testing. Interventions: Seventeen hours of group and individual training. Participants in the experimental arm received education about self-management, successful aging and an occupation-based meta-cognitive strategy-training program. Participants in the control arm received education about brain health and participated in cognitively stimulating exercises. Main measures: Changes on untrained, everyday life goals were identified using the Canadian Occupational Performance Measure. Generalization of benefits was measured using the Stanford Chronic Disease Questionnaire, general self-efficacy and changes in executive function (Delis-Kaplan Executive Function System Tower Test, Word Fluency and Trail-Making Test). Results: 20% (19/96) of healthy older adults approached were eligible, consented and were enrolled in the study, 90% (17/19) were retained to three-month follow-up. Participants in the experimental arm reported significantly more improvement on untrained goals (11/22 compared with 9/46, χ 2 =4.92, p <0.05), maintenance of physical activity ( p <0.05) and better preparation for doctors' visits ( p <0.05) relative to the control group. There were no significant between group differences on objective measures of executive function. Conclusions: These data support the feasibility of a larger trial where a sample of 72 (36 participants in each arm) would be required to confirm or refute these findings.